Aplikasi Citra Satelit QuickBird Untuk Kajian Alih Fungsi Lahan Sawah di Kota Denpasar - RUNIA CHRISTINA GULTOM; INDAYATI LANYA; I WAYAN NUARSA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2015)
ABSTRACT Quickbird Satellite Imagery Applications for study of rice field conversion in the city of Denpasar The experiment aimed to find out the rice field conversion on QuickBird satellite imagery and its relation to food availability in the city of Denpasar. This experiment was conducted in the city of Denpasar and  agricultural faculty campus, Udayana University. The method used is literature, QuickBird satellite image analysis, and food balance analysis. The result showed that  the rice field conversion by QuickBird satellite image analysis results in Denpasar, in the period of five years (2002-2006) amounted to 21 hectares, for the year 2006-2012 268,69 hectares, and for the last ten years (2002-2012) at 270,79 hectares ha. In the Year 2012 City of Denpasar has a deficit of 94.221,62 tonnes of food crops for 1 times harvest,  94.212,55 tonnes for two times harvest, and 94.203,47 tonnes for three times harvest. Denpasar City remain in deficit despite experiencing three times food crops in a year. Denpasar in 2020 deficit amounted to 100.876,57 tonnes of food for one times harvest, 100,869.00 tonnes for the two times harvest, and 100.861,43 tons for three times harvest. Like the 2020, the 2030 growing higher deficit that is 129.702,50 tonnes crop for one times harvest,  129.696,82 tonnes for the two times harvest, and 129.691,14 tonnes for three times harvest. Keywords: rice field conversion, QuickBird, satellite image, food ability,